(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the effects of different feeding systems with forage peanut (Arachis pintoi) on Corriedale lamb performance and parasitism. Three feeding systems with continuous grazing with load adjustment were evaluated: 1- animals kept exclusively on native fields; 2- animals kept on native field and two hours daily access to forage peanut pasture; 3- animals kept exclusively on forage peanut pasture. The animals were distributed in a completely randomized design with ten replications. Average weight, body mass index, body condition score, anemia level by the Famacha© method, hematocrit level and fecal eggs counts were measured. The feeding systems, degrees of parasitic infestation and their interaction were compared, in two experimental years, through analysis of variance, Fisher’s test and Kruskall-Wallis non-parametric test. Parasitic infestation was lower in 2018 regardless of the feeding system. Feeding systems using perennial peanuts showed superior animal performance and less parasitic infestation of the lambs. The use of perennial peanuts under grazing can be a tool in strategic control of worms in lambs, as long as it is integrated with other methods of parasite control. Due to climatic conditions, parasitic infestation was different in the two experimental years, regardless of the feeding systems, may be a limitation of the study.